Development of Learning Tools using Maples for Engineering Mathematics Subject - Norlenda Mohd Noor; Hanifah Sulaiman; Zuraida Alwadood; Suhaila Abd Halim; Nurul Filzah Syamimi Wahid; Nor Adilah Ab Halim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Mathematics is one of the basic and core subject for engineering students. Learning mathematics helps in developing problem solving skills as the subject requires critical thinking. However, many students perceive mathematics as a difficult subject and eventually get poor result for the subject. In the institution under study, there were increases in failure rate for the subject for the past few semesters. Based on a preliminary study, it was found that 55 percent of engineering student claimed that they encountered difficulties in visualizing functions in 3-dimensional space, which is the main content for engineering calculus subject. This fact is very unsatisfactory as engineering students are expected to possess strong mathematical problem solving skills. In light of this, the objective of this research is to develop an interactive teaching and learning tools, so as to assist students in visualizing 3-dimensional space functions. The tool is intended to be used in teaching and learning process in classrooms and it is expected that the students’ understanding in the subject could be improved.